2001
DOI: 10.1002/1521-3765(20011217)7:24<5391::aid-chem5391>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Hydrogenations of Arylalkenes Mediated by [Ir(cod)(JM-Phos)]+ Complexes

Abstract: Phosphine oxazoline ligands la-j were converted to the corresponding [Ir(cod)(phosphine oxazoline)]+ complexes 2a-j. X-ray diffraction analyses of complexes 2b, 2h, 2i, and 2j were performed. The tert-butyl-, 1,1-diphenylethyl-, and phenyl-oxazoline complexes (2b, 2h, and 2i, respectively) had typical square planar metal environments with chair-like metallocyclic rings. However, the 3,5-di-tert-butylphenyl oxazoline complex 2j was distorted toward a tetrahedral metal geometry. This library of complexes was tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
53
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(59 citation statements)
references
References 38 publications
6
53
0
Order By: Relevance
“…[4] Although iridium-PHOX catalysts gave excellent enantioselectivities and high turnover numbers in the hydrogenation of certain olefins such as 1,2-diaryl-1-alkyl-substituted alkenes, the substrate scope of these catalysts proved to be limited. Therefore, we and others started a search for new P,Nligands which enhance the application range of iridiumcatalyzed hydrogenation.Burgess and coworkers reported the JM-Phos ligands [5] (Figure 1) and, more recently, analogous oxazolines connected to an imidazolylidene instead of a phosphine group. [6] We prepared PHOX analogues (PyrPHOX; Figure 1) in which the phenyl bridge was replaced by a pyrrole ring.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[4] Although iridium-PHOX catalysts gave excellent enantioselectivities and high turnover numbers in the hydrogenation of certain olefins such as 1,2-diaryl-1-alkyl-substituted alkenes, the substrate scope of these catalysts proved to be limited. Therefore, we and others started a search for new P,Nligands which enhance the application range of iridiumcatalyzed hydrogenation.Burgess and coworkers reported the JM-Phos ligands [5] (Figure 1) and, more recently, analogous oxazolines connected to an imidazolylidene instead of a phosphine group. [6] We prepared PHOX analogues (PyrPHOX; Figure 1) in which the phenyl bridge was replaced by a pyrrole ring.…”
mentioning
confidence: 99%
“…Burgess and coworkers reported the JM-Phos ligands [5] (Figure 1) and, more recently, analogous oxazolines connected to an imidazolylidene instead of a phosphine group. [6] We prepared PHOX analogues (PyrPHOX; Figure 1) in which the phenyl bridge was replaced by a pyrrole ring.…”
mentioning
confidence: 99%
“…Extensive variations of the ligand backbone, oxazoline and phosphine groups have proved successful, although common to all these ligands is an sp 2 -hybridized coordinating nitrogen atom. Phosphorus coordination occurs most commonly via a phosphine group ( (4) [6,8] , (5) [9] , (6) [10] , (7) [11] , (11) [12] , (12) [13] , (15) [14] , (17) [15] , (20) [16] , (21) [17] and (22) [18] ), though ligands with phosphinites ( (8) [19] , (13) [20] , (14) [20,21] , (16) [22] , (18) [23] and (19) [24] ) and phosphites ( (9) and (10) [25] ) have also successfully been developed. More recently, phosphorus coordination has been replaced by the use of electron -rich N -heterocyclic carbenes [26] ( (23) [27] , (24) and (25) [28] and (26) [29] ) (Figure 2.4 ).…”
Section: Ligandsmentioning
confidence: 99%
“…Subsequently, we added phosphinoimidazolines, such as type 14, to our collection of ligands (32,33), as well as pyridine-and quinoline-derived P,N-ligands of type 15 and 16 (34), all of which gave very promising results. Recently, other research groups have become interested in this class of catalysts and have reported additional variants of Ir complexes with P,N-ligands (35)(36)(37)(38)(39)(40) and, as a further modification, oxazoline ligands with a heterocyclic carbene unit instead of a phosphino group (41). Clearly, Ir complexes derived from P,N-ligands represent a new class of catalysts that significantly expands the application range of asymmetric hydrogenation.…”
Section: Figmentioning
confidence: 99%